Harmony Unveiled: Dialogue and Cooperation with Sufism Approach as a Solution in Conflict Management Among Islamic Community Organization Cadres in Legislative Elections in Indonesia - Rizkillah, Rijal Wakhid; Supriyanto; Imron, Ali; Rohani, Imam (Taqorrub: Jurnal Bimbingan Konseling dan Dakwah, 2024)
This research departs from the problem of Islamic mass organizations which often experience conflicts between members at the time of general elections, especially when several mass organization cadres compete to run for legislative candidates. Conflicts can arise due to a variety of factors, including conflicts of interest, internal conflicts, and conflicts with other nominees, ethical conflicts, and legal conflicts. The tasawuf approach can help conflict management for mass organization cadres by teaching values such as trustworthiness, muhasabah, tawazun, makrifah, and sincerity. Tawakal can help mass organization cadres to reduce anxiety and worry about the election results. Muhasabah can help mass organization cadres to reflect on their actions and find the right solution to resolve conflicts. Tawazun can help mass organization cadres to balance personal and mass organization interests. Makrifah can help mass organization cadres understand different perspectives and respect differences. Ikhlas can help mass organization cadres to act according to correct principles and to fight for goals that are bigger than individual goals. With the tasawuf approach in conflict management, it is a new instrument as a step to reduce the intensity of organizational conflict.